Contact sensitizers trigger human CD1‐autoreactive T‐cell responses. Issue 7 (23rd May 2017) - Betts, Richard J.; Perkovic, Adrijana; Mahapatra, Subhashree; Del Bufalo, Aurélia; Camara, Kaddy; Howell, Amy R.; Martinozzi Teissier, Silvia; De Libero, Gennaro; Mori, Lucia
Abstract : Contact sensitizers, including common cosmetic compounds, are able to unleash or potentiate the capacity of antigen‐presenting cells to induce autoreactivity of skin‐associated CD1a‐restricted and CD1d‐restricted T cells. The sensitizers activity depends on endogenous lipids presented by CD1 molecules and is mediated by specific T‐cell receptors. Abstract : Allergic contact dermatitis is a primarily T‐cell‐mediated inflammatory skin disease induced by exposure to small molecular‐weight haptens, which covalently bind to proteins. The abundance of cutaneous T cells that recognize CD1a antigen‐presenting molecules raises the possibility that MHC‐independent antigen presentation may be relevant in some hapten‐driven immune responses. Here we examine the ability of contact sensitizers to influence CD1‐restricted immunity. Exposure of human antigen‐presenting cells such as monocyte‐derived dendritic cells and THP‐1 cells to the prototypical contact sensitizer dinitrochlorobenzene potentiated the response of CD1a‐ and CD1d‐autoreactive T cells, which released a vast array of cytokines in a CD1‐ and TCR‐dependent manner. The potentiating effects of dinitrochlorobenzene depended upon newly synthesized CD1 molecules and the presence of endogenous stimulatory lipids. Further examination of a broad panel of contact sensitizers revealed 1, 4‐benzoquinone, resorcinol, isoeugenol, and cinnamaldehyde to activate the same type of CD1‐restricted responses. These findings provide a basis for the antigen‐specific activation of skin‐associated CD1‐restricted T cells by small molecules and may have implications for contact sensitizer‐induced inflammatory skin diseases.